Pleistocene and Holocene palaeoclimates in the Gebel Akhdar (Libya) estimated using herbivore tooth enamel oxygen isotope compositions. (6th June 2016) - Reade, Hazel; O'Connell, Tamsin C.; Barker, Graeme; Stevens, Rhiannon E.
Abstract: The palaeoclimate of the Gebel Akhdar massif, in Cyrenaica, northeast Libya, is investigated using the stable oxygen isotope ratio (δ 18 O) of herbivore tooth enamel from the archaeological faunal assemblages of the Haua Fteah and Hagfet ed Dabba caves. Samples accumulated through human activity at the sites, thus climatic interpretations are in direct chronological association with periods of human presence in the local landscape. Wild Ammotragus lervia (Barbary sheep) and Bos sp. (auroch), and domestic Ovis sp. and Capra sp. from the Levalloiso-Mousterian (≥73.3–43.5 ka) to the Neolithic (∼9.3–5.4 ka) cultural phases are analysed. Results indicate that the most arid environment represented by the samples occurred at ∼32 ka, when populations associated with Dabban lithic assemblages were present within the region. Climatic instability increased during oxygen isotope stage 2. Consistent with other palaeoenvironmental investigations in the Gebel Akhdar, there is no evidence for hyper-arid events during the last glacial and surface water, most probably in the form of local springs, was available throughout the time periods considered. Overall, results indicate that different cultural groups occupied the Gebel Akhdar landscape under different climatic conditions, but that climate variations appear to have been of lower magnitude than those that occurred at inland North African locations. These reconstructions provide further support to the theory that the Gebel Akhdar may have served as a refugium for human populations in North Africa during times of global climatic extremes.